The effect of seed health of perennial ryegrass (Lolium perenne L.) on germination capacity - Wiewióra, Barbara (Plant Breeding and Seed Science, 2012)
The analysis of seed health and germination capacity of 7 varieties of Lolium perenne, originated from two breeding station and two seed company localized in different places of Poland, harvested in 2006, 2007 and 2008 were performed. Results of mentioned analysis indicated that seeds were contaminated by numerous species of fungi. The most numerous group of fungi were saprophytes or weak parasites such as: Alternaria alternata, Epicoccum nigrum, Septonema chaetospira and Penicillium spp. Pathogenic species were represented by species of Drechslera, Fusarium, Phoma, Curvularia lunata and Bipolaris sorokiniana. Seed germination capacity was inﬂuenced by contamination of fungi. It was found that seed more often contaminated by fungi germinated much poorer then seed with lower infection.